Pendampingan program penanggulangan TB paru dengan aplikasi sistem informasi pemantauan pengobatan pasien tuberkulosis paru (SISFOTBPARU) - Trigunarso, Sri Indra; Muslim, Zainal; Hasan, Amrul (JOURNAL of Public Health Concerns, 2025)
Background: Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. It is estimated that approximately one-quarter of the world's population has been infected with the TB bacteria. Generally, people infected with TB do not feel sick and are not contagious. The Indonesian Ministry of Health is maximizing efforts by creating a national standard that serves as a benchmark for all healthcare workers in handling pulmonary TB cases. The development of a digital application program is essential to obtain up-to-date and real-time data, enabling healthcare workers to intervene more accurately and expeditiously in handling and managing TB cases. Purpose: To provide knowledge and assistance in using the pulmonary tuberculosis patient treatment monitoring information system (SISFOTBPARU) application. Method: Community service activities were conducted in the P2TB Section of 10 Community Health Centers in Bandar Lampung City, with data input from 10 Community Health Centers in Bandar Lampung City, Lampung Province. Participants were 30 Community Health Center TB officers and PMOs. The educational activities provided participants with understanding and knowledge in implementing and developing a pulmonary tuberculosis patient treatment monitoring information system (SISFOTBPARU). Participants' knowledge and skills after the education were measured using a system usability scale (SUS) questionnaire. Results: The system usability scale (SUS) test showed that 9 participants (30.0%) were in the very good and accepting category, 10 (33.3%) were in the good and accepting category, and 11 (36.7%) were in the good but passive acceptance category. The score of 89.76, with an acceptability range classified as marginally high, graded on the scales, indicated a very good level of usability. Conclusion: Educational and mentoring activities in the implementation of the Pulmonary Tuberculosis Patient Treatment Monitoring Information System (SISFOTBPARU) application have positively contributed to the monitoring and treatment of pulmonary tuberculosis patients. The SISFOTBPARU application also improves the effectiveness of healthcare workers in monitoring and treating pulmonary tuberculosis patients. Suggestion: The SISFOTBPARU application is expected to be implemented sustainably and across a wider range of community health centers (Puskesmas). The application developers are also expected to continue improving the SISFOTBPARU application by keeping up with the latest technological developments. Keywords: Application implementation; Community health; Education and mentoring; Pulmonary tuberculosis Pendahuluan: Tuberkulosis adalah suatu penyakit menular yang disebabkan oleh kuman mycobacterium tuberculosis. Diperkirakan sekitar seperempat populasi dunia telah terinfeksi bakteri TB. Umumnya, orang yang terinfeksi TB tidak merasa sakit dan tidak menular. Kementerian Kesehatan Republik Indonesia memaksimalkan upaya dengan menciptakan suatu standar secara nasional yang menjadi patokan untuk setiap tenaga kesehatan dalam melakukan penanganan kasus TB Paru. Pengembangan program berupa aplikasi digital harus dilakukan untuk mendapatkan data yang up to date dan secara realtime dapat di akses, agar penanganan dan penanggulangan kasus TB menjadi lebih tepat dan cepat bagi petugas kesehatan untuk melakukan intervensi. Tujuan: Memberikan pengetahuan dengan pendampingan dalam menggunakan aplikasi sistem informasi pemantauan pengobatan pasien tuberkulosis paru (SISFOTBPARU). Metode: Kegiatan pengabdian kepada masyarakat dilaksanakan di Seksi P2TB 10 Puskesmas Kota Bandar Lampung dengan input data berasal dari 10 Puskesmas Kota Bandar Lampung, Propinsi Lampung. Peserta kegiatan adalah petugas TB Paru Puskesmas dan PMO dengan jumlah 30 orang. Kegiatan berupa edukasi memberikan pemahaman dan pengetahuan kepada peserta dalam menerapkan dan pengembangan aplikasi sistem informasi pemantauan pengobatan pasien tuberkulosis paru (SISFOTBPARU). Pengukuran tingkat pengetahuan dan kemampuan peserta setelah edukasi yang diberikan menggunakan kuesioner system usability scale (SUS). Hasil: Berdasarkan uji system usability scale (SUS) menunjukkan bahwa peserta yang dalam kategori sangat baik dan dapat menerima adalah sebanyak 9 orang (30.0%), yang dalam kategori baik dan dapat menerima adalah sebanyak 10 orang (33.3%), dan yang dalam kategori baik tetapi pasif menerima adalah sebanyak 11 orang (36.7%). Hasil skor 89.76 dengan acceptability ranges tergolong marginal high, grade scales termasuk nilai A, dan mengindikasikan tingkat usability yang sangat baik. Simpulan: Kegiatan edukasi dan pendampingan dalam penerapan aplikasi sistem informasi pemantauan pengobatan pasien tuberkulosis paru (SISFOTBPARU) memberikan kontribusi positif terhadap pemantauan dan pengobatan pasien tuberkulosis paru. Aplikasi SISFOTBPARU juga memberikan peningkatan efektifitas kinerja petugas kesehatan dalam melaksanakan pemantauan dan pengobatan pasien tuberkulosis paru. Saran: Diharapkan aplikasi SISFOTBPARU dapat diterapkan secara berkelanjutan dan untuk sebaran wilayah Puskesmas yang lebih luas. Diharapkan juga kepada pihak pengembang aplikasi, untuk terus membuat aplikasi SISFOTBPARU agar menjadi lebih sempurna dengan mengikuti perkembangan teknologi terbaru.